Intuitive eating for every day : 365 daily practices & inspirations to rediscover the pleasures of eating - Tribole, Evelyn, 1959- (Chronicle Prism, 2021)
"Intuitive Eating for Every Day: 365 Daily Meditations and Inspirations for Making Peace with Food Intuitive Eating is a true lifestyle change. It's a journey of self-discovery, awareness, and letting go of diet culture. It will heal your relationship with food, your mind, and help you re-connect with your own body. Ultimately, it will liberate you from a world obsessed with appearance and ground you in your feelings and thoughts. This book of meditations and inspirations will be your ally against a world steeped in diet culture. It will guide, illuminate, and encourage your Intuitive Eating"--